Advances in the derivation of fragility functions for the development of risk-targeted hazard maps. (15th October 2018) - Martins, Luís; Silva, Vítor; Bazzurro, Paolo; Marques, Mário
Highlights: Influence of fragility parameters on the context of a Risk-targeted hazard assessment. FE model and nonlinear time history analyses used to assess structural fragility. Models to compute fragility functions directly from the design ground motion are proposed. PDF fitted to the probability of collapse at design ground motion ( Pc |ades ). Propagation of uncertainties on the fragility models to final risk metrics. Abstract: Risk-targeted hazard assessment aims at estimating the design ground shaking that leads to a uniform distribution of the collapse probability of buildings within a given region. An essential aspect of this methodology relies on the definition of the relationship between the collapse probability of buildings designed according to modern seismic regulations and the considered design ground motion. This study adds to previous research on the topic of seismic risk-targeted hazard assessment by investigating how the collapse probability varies with the design level of ground motion, and how this variability influences the resulting seismic risk across Europe. A large number of structures designed according to the most recent seismic regulation in Europe have been analysed. These structures were designed for increasing levels of peak ground acceleration ranging from values close to zero (i.e. buildings located in regions with very low seismic hazard) up to 0.40 g (i.e. moderate to high seismic hazard). Each structure was modelled as a tri-dimensional finite element model, and tested against a set of ground motion records using nonlinear dynamic analyses. Several fragility functions were derived for yielding and collapse damage states, and combined with the seismic hazard curves from the European project SHARE to calculate the spatial distribution of earthquake risk across Europe.